2014
DOI: 10.1007/s00253-014-6241-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the hydrogen partial pressure on lactate degradation in a coculture of Desulfovibrio sp. G11 and Methanobrevibacter arboriphilus DH1

Abstract: In this study, the impact of the hydrogen partial pressure on lactate degradation was investigated in a coculture of Desulfovibrio sp. G11 and Methanobrevibacter arboriphilus DH1. To impose a change of the hydrogen partial pressure, formate was added to the reactor. Hydrogen results from the bioconversion of formate besides lactate in the liquid phase. In the presence of a hydrogen-consuming methanogen, this approach allows for a better estimation of low dissolved hydrogen concentrations than under conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
1
17
1
Order By: Relevance
“…One interpretation of the broad scope of the phenotypic changes occurring in response to the cooA deletion is that central metabolism has been perturbed. Possibly hydrogen oxidation (part of the "hydrogen transient" when D. vulgaris is grown with organic acids (Noguera et al, 1998)) could be preferentially inhibited by CO causing an increase in hydrogen concentration that prohibits lactate degradation, already thermodynamically unfavourable ( Junicke, Feldman, van Loosdrecht, & Kleerebezem, 2014). Rajeev and co-workers successfully complemented the deletion of cooA with a wild-type cooA encoded on a plasmid restoring growth with lactate/sulphate in the presence of CO .…”
Section: Computational Predictionsmentioning
confidence: 97%
“…One interpretation of the broad scope of the phenotypic changes occurring in response to the cooA deletion is that central metabolism has been perturbed. Possibly hydrogen oxidation (part of the "hydrogen transient" when D. vulgaris is grown with organic acids (Noguera et al, 1998)) could be preferentially inhibited by CO causing an increase in hydrogen concentration that prohibits lactate degradation, already thermodynamically unfavourable ( Junicke, Feldman, van Loosdrecht, & Kleerebezem, 2014). Rajeev and co-workers successfully complemented the deletion of cooA with a wild-type cooA encoded on a plasmid restoring growth with lactate/sulphate in the presence of CO .…”
Section: Computational Predictionsmentioning
confidence: 97%
“…This study showed experimental evidence for the previously formulated concept by Junicke et al () that the acetogen can be the growth‐limiting partner in a syntrophic methanogenic coculture on lactate. This defined coculture study, illustrates the need for an accurate measurement of individual biomass amounts, as otherwise the distribution of biomass‐specific fluxes would lack a final proof.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate whether the partial reactions shown in Table are thermodynamically favorable under the prevailing experimental conditions, the actual Gibbs energy change (Δ G 1 ) was calculated according to ΔG1=ΔG01+RTnormalYnormaliInnormalcnormali where Δ G 01 is the Gibbs energy change at 310.15 K and pH 7.0, Y i denotes the stoichiometric coefficient and c i the concentration of compound i. T denotes the temperature in Kelvin and R the gas constant (8.314 J/K/mol). A more detailed model description is given in Junicke et al ().…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations